Pandemic Lockdowns as A Risk Factor in The DCF Process – Proposed Solution for Cash Flow Adjustments - Piotr DABROWSKI; Witold GRADON (Communications of International Proceedings, 2021)
Pandemic lockdowns directly affect the cash flows of companies, especially in the tourism industry, and should therefore be included in the valuation process in order to properly reflect the risk of lockdowns. The objective of the research is analysis of the financial parameters of the tourism industry during the pandemic. As a result, we propose specific adjustments to incomes and costs for cash flow forecasts in DCF model valuation.
Keywords: : DCF; Valuation; Pandemic; Cash Flow Adjustments; Risk Factor